Análise numérica da força última e do modo de falha de ligações com cisalhamento duplo em estruturas de madeira - Leoni, Vitor Lourensato (Universidade Federal de São Carlos, 2023)
Timber is a material with several benefits for the construction industry because, in addition to being sustainable and renewable, it also possesses favorable properties for use in structures. However, precisely because it is a natural material, the vast number of wood species and their varying mechanical properties pose challenges for research. Consequently, this present study undertook a comprehensive numerical analysis employing the ABAQUS software to investigate some wood species and their performance in structural connections involving metallic pins under double shear conditions. The principal objective of this study was to evaluate the precision of normative equations and pertinent literature. In light of this, regression models were employed to formulate an equation capable of estimating the ultimate strength and failure mode of these connections. Two regression models, characterized by determination coefficients of 95.74% and 91.50% respectively, were successfully derived, clearly illustrating the significant influence of all analyzed parameters on the calculated values of ultimate strength. This approach facilitated a meticulous comparison of the precision exhibited by these parameter equations, effectively identifying any divergences that may exist between the models integrated into normative codes, such as ABNT NBR 7190-1 (2022) and EUROCODE 5 (2004), and the results acquired through this research results. Conspicuous disparities were observed, particularly when contrasting the theoretical outcomes obtained from the Brazilian normative code with all other calculated values. These findings compellingly suggest that the values generated by normative equations are overly cautious in nature.
Numerical analysis of ultimate force and failure mode of double shear connections in timber structures
Keywords: Madeira; Ligações tipo cavilha; ABAQUS; Modo de falha; Força última; Timber; Dowel connections; Failure mode; Ultimate strength; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL::MATERIAIS E COMPONENTES DE CONSTRUCAO; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS::ESTRUTURAS DE MADEIRAS; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS::MECANICA DAS ESTRUTURAS